2008
DOI: 10.1182/blood-2007-02-074716
|View full text |Cite
|
Sign up to set email alerts
|

NK-cell activation and antibody-dependent cellular cytotoxicity induced by rituximab-coated target cells is inhibited by the C3b component of complement

Abstract: Antibody-dependent cellular cytotoxicity (ADCC) and complement fixation both appear to play a role in mediating antitumor effects of monoclonal antibodies (mAbs), including rituximab. We evaluated the relationship between rituximabinduced complement fixation, natural killer (NK)-cell activation, and NK cellmediated ADCC. Down-modulation of NKcell CD16 and NK-cell activation induced by rituximab-coated target cells was blocked by human serum but not heatinactivated serum. This inhibition was also observed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
139
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(148 citation statements)
references
References 43 publications
7
139
2
Order By: Relevance
“…Moreover, by a strategy of local fH inhibition, putative systemic side effects of an anti-fH strategy may also be reduced. We do not expect that the increased complement activation and thus enhanced C3b deposition will decrease the overall efficacy of ofatumumab by impairing natural killer cell-mediated ADCC 45 as recently published data indicate that monoclonal antibody-dependent amplification of C3 deposition on tumor cells enhanced both macrophagedependent, Fc-mediated ADCC and CDC in vitro and in vivo. 46 Thus, the lack of natural killer cell activation can be compensated for by increased phagocytosis and complement-mediated lysis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, by a strategy of local fH inhibition, putative systemic side effects of an anti-fH strategy may also be reduced. We do not expect that the increased complement activation and thus enhanced C3b deposition will decrease the overall efficacy of ofatumumab by impairing natural killer cell-mediated ADCC 45 as recently published data indicate that monoclonal antibody-dependent amplification of C3 deposition on tumor cells enhanced both macrophagedependent, Fc-mediated ADCC and CDC in vitro and in vivo. 46 Thus, the lack of natural killer cell activation can be compensated for by increased phagocytosis and complement-mediated lysis.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in contrast to human IgG1, the format of Ab used by almost all approved Ab drugs, which at least in vitro mediates target cell killing mainly by recruiting NK cells as effector cells or by complement fixation. For rituximab, first-infusion reactions were correlated with the activation of complement (38), whereas the therapeutic contribution of CDC to the antitumor activity of rituximab in patients remains to be investigated (39,40). Our Ab construct, which does not activate human complement, might be an attractive alternative for clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Further functional assays confirmed that complement fixation upstream of C5 is responsible for the impaired ADCC activity mediated by NK cells in the presence of serum. 72 In addition, NK-mediated ADCC capacity of the glycoengineered mAb obinutuzumab (GA101), having a decreased ability to fix complement compared with rituximab, was not affected in the presence of complement. 73 To confirm those findings in vivo, a murine anti-idiotype mAb directed against murine 38C13 B cell lymphomas was used to show that serum blocks murine NK cell activation.…”
Section: The Role Of Complement In Ab Immunotherapymentioning
confidence: 99%